2023
DOI: 10.1097/mol.0000000000000875
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-rich lipoproteins, remnant-cholesterol, and atherosclerotic cardiovascular disease

Abstract: Purpose of reviewDespite indisputable role of LDL-C lowering, a considerable residual risk for atherosclerotic cardiovascular disease (ASCVD) persists. The precise mechanism(s) underlying this phenomenon remain unclear. Triglyceride-rich lipoproteins (TRL) appear to be one of the main mediators, based on the genetic and epidemiologic data. However, whether this is caused by direct effects of Triglycerides or other components of TRL remains uncertain. The cholesterol component of TRL remnants (Rem-C) has been p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Together, these activities produce particles known as remnants, with the primary structural proteins of chylomicron and VLDL remnants, respectively, being retained by apoB48 and apoB100. In the case of VLDL remnants, these consist of a group of particles known as intermediate-density lipoproteins (IDLs), with a density (d) of 1.006–1.019 g/mL and an analytical ultracentrifuge flotation rate (Sf) of 12–20, which has been demonstrated to overlap in distribution with small VLDL particles with d 1.006 g/mL and Sf 20–60 [ 7 , 12 , 37 , 38 , 39 , 69 ].…”
Section: The Second Phase Of the Fluxes Of Trls: Enabling The Uptake ...mentioning
confidence: 99%
“…Together, these activities produce particles known as remnants, with the primary structural proteins of chylomicron and VLDL remnants, respectively, being retained by apoB48 and apoB100. In the case of VLDL remnants, these consist of a group of particles known as intermediate-density lipoproteins (IDLs), with a density (d) of 1.006–1.019 g/mL and an analytical ultracentrifuge flotation rate (Sf) of 12–20, which has been demonstrated to overlap in distribution with small VLDL particles with d 1.006 g/mL and Sf 20–60 [ 7 , 12 , 37 , 38 , 39 , 69 ].…”
Section: The Second Phase Of the Fluxes Of Trls: Enabling The Uptake ...mentioning
confidence: 99%
“…In this study, mediation via systemic inflammation seemed plausible, as triglyceride contents of LDL, HDL and the respective particles were associated with higher CRP levels. In agreement, a recent review based on results from the Copenhagen City study reported that triglyceride-rich lipoproteins caused systemic low-grade inflammation (Ganda, 2023). In line with increased chronic inflammation, it has been argued that systemic inflammation alters the microenvironment in the periodontal pocket, favouring a shift to a dysbiotic microbiome (Van Dyke et al, 2020).…”
Section: Discussionmentioning
confidence: 65%
“…The limitation is that it is not possible to separate remnants using DGU alone. Undeniably, remnant particles produced by the lipolysis of newly synthesized postprandial lipoproteins, CM and VLDL, cover nearly the whole spectrum of lipoprotein densities ( 1 , 9 , 149 ).…”
Section: Clinical and Research Testing Of Postprandial Lipoprotein Me...mentioning
confidence: 99%